Gemma Bovery [videorecording (DVD)] - Simmonds, Posy; Arterton, Gemma; Luchini, Fabrice, 1951-; Flemyng, Jason (Music Box Films, 2015)
Having moved to a rustic farm with her older husband, Gemma soon tires of their simpler life and finds distraction in a torrid affair with a handsome young aristocrat. Meanwhile, Martin, a local baker and lover of literature, becomes besotted with Gemma, but also fears she may suffer the same fate as the heroine in his favorite novel.